Comparison of Eye Detection Methods using Image Processing - Biradar, Vijayalaxmi (International Journal of Engineering and Technology, 2018)
Driver fatigue is major factor in more number of vehicle accidents on road.Â  Statistics from Transport Accident Commission shows that nearly 20% of fatal road accidents involve fatigue. National Highway Traffic Safety Administration estimate that nearly 2,000 deaths, 70,000 injuries and $12.5 billion of financial losses occur annually. The development of technologies for detecting and preventing fatigue at the wheel is a major challenge faced by accident avoidance systems. Measurement of fatigue becomes difficult as it becomes more pronounced. During last decade, lot of research work has been carried out development of fatigue detection system for avoiding accidents on road. It is the summary of all related work carried out, the methods and components required in this research. The drawbacks of the existing methods, advantages and limitations are discussed in this paper. There are many technologies for Fatigue detection which are divided into biological indicators, vehicle behaviour and face analysis. This paper is a part of research work on the project â€œDevelopment of Non-Intrusive Driver Fatigue Detection & Warning System to avoid on road Accidentsâ€ sanctioned under Early Career Research Award sponsored by Science & Engineering Research Board ,Govt. of India ,New Delhi at Vignan Institute of Technology & Science, Vignan Hills, Hyderabad.Â Â
Keywords: Face; Eye; Driver; Fatigue; Skin